Yield emulsifiers exopolysaccharides produced by native halophilic bacteria concentrations molasses three Saccharum officinarum L. "sugarcane" - Fuentes, Ángel (2013)
The microbial exopolysaccharide with emulsifying properties are an alternative to polymers and chemicals from algae and plants. Its production in molasses as carbon source lowers costs and generates added value to this byproduct of the sugar industry, so the aim of this study was to determine the performance and productivity of EPS emulsifiers by native halophilic bacteria in 20, 30 and 40 gL-1 of molasses. In MY synthetic medium with 5 % w/v of salts, 138 isolates of bacteria obtained from soil samples of salt water and in the districts of San Jose and Santa Rosa, in Lambayeque. In 10.8 % of these gummy colony forming bacteria and grown on glucose as carbon source EPS recovered whose maximum values of the mixtures in water emulsion - oil phase were 63.3 and 56.6 % after 1 and 24 hours, respectively. The M5 bacteria identified as Halomonas C1 10-1 sp. M5 EPS synthesized emulsifiers molasses broth, reaching yields Yp/s of 0.296 gg-1 and 0.200 gg-1 with 20 and 30 gL-1 of molasses respectively, a productivity of 0.016 and 0.017 gL-1 h -1 , not differing significantly between them. With 10 gL-1 glucose was reached Yp/s of 0.171 gg-1 and a productivity of 0.018 gL-1 h -1 . It was shown that the EPS produced native halophilic bacteria utilizing molasses emulsifiers as carbon source.